Fractional Exhaled Nitric Oxide (FENO) in the management of asthma: a position paper of the Italian Respiratory Society (SIP/IRS) and Italian Society of Allergy, Asthma and Clinical Immunology (SIAAIC) - Heffler, Enrico; Carpagnano, Giovanna Elisiana; Favero, Elisabetta; Guida, Giuseppe; Maniscalco, Mauro; Motta, Andrea; Paoletti, Giovanni; Rolla, Giovanni; Baraldi, Eugenio; Pezzella, Vincenza; Piacentini, Giorgio; Nardini, Stefano (Multidisciplinary respiratory medicine, 2020)
Asthma prevalence in Italy is on the rise and is estimated to be over 6% of the general population. The diagnosis of asthma can be challenging and elusive, especially in children and the last two decades has brought evidences that asthma is not a single disease but consists of various phenotypes. Symptoms can be underestimated by the patient or underreported to the clinician and physical signs can be scanty. Usual objective measures, like spirometry, are necessary but sometimes not significant. Despite proper treatment, asthma can be a very severe condition (even leading to death), however new drugs have recently become available which can be very effective in its control. Since asthma is currently thought to be caused by inflammation, a direct measure of the latter can be of paramount importance. For this purpose, the measurement of Fractional Exhaled Nitric Oxide (FE ) has been used since the early years of the current century as a non-invasive, easy-to-assess tool useful for diagnosing and managing asthma. This SIP-IRS/SIAAIC Position Paper is a narrative review which summarizes the evidence behind the usefulness of FE in the diagnosis, management and phenotypization of asthma.